Perancangan UI/UX Prototype Sistem Informasi Pendataan Tamu di Sebuah Perusahaan Berbasis Website Menggunakan Metode Design Thinking - Adi Subekti; Firamon Syakti (CV. ALIM'SPUBLISHING, 2026)
Guest data collection is an important administrative activity in supporting the management of visitor information in a company. However, the manual guest data collection process often causes various obstacles, such as recording errors, difficulty in searching for data, and ineffective reporting processes. This study aims to design the User Interface (UI) and User Experience (UX) prototype for a website-based Guest Data Collection Information System using the Design Thinking method. The Design Thinking method was chosen because it is oriented towards user needs through five stages: empathize, define, ideate, prototype, and test. Data collection was carried out through observation and identification of user needs for the guest data collection system. The results of the study are an interface prototype designed using Figma, consisting of a login page, dashboard, guest data collection, guest data, and reports. The resulting prototype is expected to provide an overview of a system that is easier to use, has clear navigation, and supports the guest data collection process more effectively. This research can be a reference in the development of a guest data collection information system in the next implementation stage.